Characterization and function analysis of interleukin-1 receptor-associated kinase-1 (IRAK-1) from Fenneropenaeus penicillatus. Issue 61 (February 2017) - Xu, Youhou; Huang, Yucong; Cai, Shuanghu
Abstract: The interleukin-1 receptor-associated kinase-1 (IRAK-1) is an important adapter protein which links downstream of MyD88, and involved in the complex composed of MyD88 and TRAF6 to activate TLRs signaling pathway. In this study, an IRAK-1 homolog (FpIRAK-1) was cloned from the red tail shrimp Fenneropenaeus penicillatus . The ORF of FpIRAK-1 consisted of 2874 bp encoding a protein of 957 amino acids which contains a death domain (DD) and a catalytic domain of serine/threonine kinases (STKc). Homology analysis revealed that the predicted amino acid sequence of FpIRAK-1 shared 71% similarities with IRAK-1 of Litopenaeus vannamei . Real-time RT-PCR indicated that FpIRAK-1 was constitutively expressed in various tissues of F. penicillatus . The expression level of FpIRAK-1 mRNA was significantly up-regulated and then decreased gradually after white spot syndrome virus (WSSV) and Vibrio alginolyticus challenge. Gene knockdown of FpIRAK-1 enhanced the sensitivity of shrimps to WSSV and V. alginolyticus challenge, suggesting FpIRAK-1 could play a positive role against bacterial and viral pathogens. In conclusion, the results of this study provide some insights into the function of FpIRAK-1 in activating Toll signaling pathway and the host defense against invading pathogens. Highlights: An IRAK-1 homolog (FpIRAK-1) was cloned from the red tail shrimp F. penicillatus. FpIRAK-1 was constitutively expressed in various tissues of F. penicillatus. The expression levels of FpIRAK-1 mRNA in the different tissues are responsive to WSSV and V. alginolyticus challenge. Gene knockdown of FpIRAK-1 enhanced the sensitivity of shrimps to WSSV and V. alginolyticus challenge.